The Extent to Which Public Universities in Kenya Experience Managerial and Environmental Challenges - Mathooko, F. M.; Ogutu, Martin (European Journal of Business and Management, 2014)
The environment in which organisations operate is continuously changing, thereby posing challenges to the organisations, and higher education institutions are no exception. This study was undertaken to understand the managerial and environmental challenges faced by public universities in Kenya. The study design was descriptive and utilized a cross-sectional survey of all the public universities in Kenya through administration of a structured questionnaire to the top management team. Secondary data were collected from published works and, universities and government documents in public domain in order to corroborate the data collected from the primary sources. Positive responses were received from 63 respondents out of 91, yielding a 69.4 percent response rate. Of the respondents, 76 percent had basic training in the sciences and only 3 percent in business; 79 percent had no training in management and only 8 percent each had training in management at postgraduate diploma and postgraduate degree levels. The universities faced managerial challenges ‘to a greater extent’ than they faced environmental challenges. The control function of management, and competitive and economic macro-economic factors posed the highest challenges. A significant difference (p<0.05) in the managerial and environmental challenges existed between new and old universities, and rural and urban universities, respectively. There was significant difference (p<0.05) and no significant difference (p<0.05) among the three categories of public universities (old, new and university colleges) in managerial and environmental challenges, respectively. The results indicate that the managerial and environmental challenges experienced by public universities in Kenya could be related to lack of training in management. The results further indicate that public universities in Kenya are dependent on the environment in which they operate and, therefore, the studycontributes to the environment-dependence theory of organizations.
Keywords: Environmental challenge; environment-dependence theory; higher education institutions; Kenya; managerial challenge; public university